The structure of services in correctional institutions in the light of the structural-functional theory: Analytical theory study - Ahmed, Karwan; Ghafur, Rzgar (Al-Adab Journal, 2023)
Punitive institutions are considered among the social institutions that seek to achieve their preventive goals by rehabilitating criminals in order to preserve the internal system of this institution, and in application of the applicable social policy aimed at bringing about a change in the behavior of individuals. The researcher in the current study followed the desk reaserches when reviewing the literature and sources in his study Theory. The researcher employed the structural and functional theory in explaining and clarifying the services provided in the correctional institutions. Through the structural-functional theory, the institution's practice of its functions is based on an institutional structure that is progressive and conscious of its performance of functions. Therefore, the relationship between the inmate and the institution is a conscious relationship, meaning that it is specific, and the institution is his awareness of the extent of the services it provides to him. The constructive-functional approach begins in its analysis of the prison by looking at it as a geographical environment for a human society, in which those in it have stable, solid and similar relationships with their counterparts in every prison in the world, regardless of its location, type and nationality of its inmates